Factor Validation of the Staff Perceptions of Behavior and Discipline (SPBD) Survey. (February 2019) - Feuerborn, Laura L.; Tyre, Ashli D.; Zečević, Mladen
The implementation of schoolwide positive behavior interventions and supports (SWPBIS) requires a shift from a reliance on reactionary discipline to prevention-oriented supports, and it requires that staff adopt and regularly apply the practices throughout the building. This level of systemic change in staff thinking and practice is challenging to achieve and sustain, but data can assist teams in navigating the process. The Staff Perceptions of Behavior and Discipline (SPBD) is a needs assessment survey developed to measure staff beliefs, needs, and concerns for discipline and behavioral support practices. This tool can help teams make data-informed decisions, and target professional development to fit the needs and concerns of staff in their building. This study reexamines the internal consistency and factor structure of the SPBD using an expanded data set of 147 schools, including elementary, middle, and high schools across several geographic regions in the United States. The results corroborate the SPBD's existing factor structure over alternative factor structures and support the internal consistency of each subscale. Implications for practice and future research are provided.